Asthma severity and heterogeneity: Insights from prevalence trends and associated demographic variables and anthropometric indices among Israeli adolescents. (3rd August 2018) - Machluf, Yossy; Farkash, Rivka; Fink, Daniel; Chaiter, Yoram
ABSTRACT: Objectives : While asthma presents various clinical forms with different levels of severity, it is unclear whether asthma severities are a consequence of disease management or varied etiologies. We sought to investigate this question. Methods : This paper presents a cross-sectional study of 113, 671 Israeli adolescents. Prevalence rates of mild and moderate-to-severe asthma over a 24-year period were calculated and multivariate regression models (outcomes: different asthma severity, reference: subjects without asthma) were performed to analyze associations with anthropometric indices and socio-demographic variables, in males and females separately. Results : The prevalence of mild asthma increased until birth years 1976–1980 and then steadily decreased. In contrast, the prevalence of moderate-to-severe asthma was relatively stable until birth years 1976–1980, then rose steeply until 1986–1990 and subsequently plateaued in the early 1990s. Obesity was positively associated with both mild and moderate-to-severe asthma in males (Odds Ratio (OR) [95%CIs]: 1.61 [1.37–1.89] and 1.63 [1.34–1.98], respectively) and females (1.54 [1.10–2.16] and 1.54 [1.20–1.98], respectively). Family size greater than three siblings was negatively associated with both mild and moderate-to-severe asthma in males (0.62 [0.56–0.68] and 0.59 [0.52–0.68]) and females (0.71 [0.60–0.83] and 0.73 [0.63–0.83]). In contrast, in males, underweight was only associated with mild asthma (1.54 [1.22–1.94]) but not with moderate-to-severe asthma. In females, overweight was only associated with moderate-to-severe asthma (1.21 [1.00–1.46]) and rural residence was only associated with mild asthma (1.26 [1.09–1.47]). Conclusions : The differences between mild and moderate-to-severe asthma enhance asthma phenotype characterization, with respect to secular trends and associated variables, and indicate varied etiologies.